2022
DOI: 10.3390/polym14122381
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Timber Structural Members with CFRP and GFRP: A State-of-the-Art Review

Abstract: The application of fibre-reinforced polymers (FRP) for strengthening timber structures has proven its efficiency in enhancing load-bearing capacity and, in some cases, the stiffness of structural elements, thus providing cost-effective and competitive alternatives both in new design and retrofitting existing historical buildings. Over the last few decades, several reinforcing materials and techniques evolved, and considerable progress was made in numerical modelling, especially using the finite element method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 135 publications
(191 reference statements)
1
11
0
Order By: Relevance
“…Several authors reported a low or moderate increase in stiffness resulting from FRP reinforcement. In a number of cases, the measured and predicted values significantly differ, as shown in a review article [ 26 ]. Therefore, we propose to improve the modelling by considering different moduli for tension ( ) and compression ( ) in timber.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors reported a low or moderate increase in stiffness resulting from FRP reinforcement. In a number of cases, the measured and predicted values significantly differ, as shown in a review article [ 26 ]. Therefore, we propose to improve the modelling by considering different moduli for tension ( ) and compression ( ) in timber.…”
Section: Methodsmentioning
confidence: 99%
“…It is apparent that results are scattered in a wide range and sometimes contradict expectations. A review comparison between the measured stiffness increase and the theoretical values obtained from calculations using classical beam theory was shown in [ 26 ] based on several research works processed. In some studies, the increase agreed with the theoretical estimates, e.g., [ 17 , 27 , 28 ], while the results contradicted the theoretical expectations in many other studies, e.g., [ 23 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…CFRP can be used in some engineering with high bearing capacity and harsh corrosion environments due to its very excellent mechanical properties, fatigue resistance, and corrosion resistance even though it is a high price. While GFRP showed good mechanical properties with a low price, however, the long-term corrosion resistance and fatigue resistance are weak when facing some complex environmental exposure [ 1 , 2 , 3 ]. Over the past few years, the desire for fiber-reinforced polymer composites (non-metallic) has increased for dental fiber post applications such as carbon fiber, quartz fiber, and glass fiber posts to replace metallic posts due to the drawbacks of metallic posts, including their propensity for corrosion, root fractures, and loss of retention, as well as the rising desire for cosmetic restorations, all ceramic crowns must be supported by aesthetic posts [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…CFRP is durable, easily stick to timber and they are low-density materials. Besides, when they are used on the tension side of timber element, a significant amount of tensile stress is transferred from timber under bending which is allowing the timber compression side to yield 32 .…”
Section: Introductionmentioning
confidence: 99%